SMI-Ribosome inactivating protein conjugates selectively inhibit tumor cell growth. Issue 30 (30th March 2017) - Roy, Saumya; Axup, Jun Y.; Forsyth, Jane S.; Goswami, Rajib K.; Hutchins, Benjamin M.; Bajuri, Krishna M.; Kazane, Stephanie A.; Smider, Vaughn V.; Felding, Brunhilde H.; Sinha, Subhash C.
Abstract : Cell-targeting conjugates of Saporin 6, prepared using a small molecule inhibitor of integrins αv β3 and αv β5 and the Saporin A157C mutant, selectively and potently inhibited proliferation of tumor cells expressing the target integrins. Abstract : Cell-targeting conjugates of Saporin 6, a ribosome inactivating protein (RIP), were prepared using the Saporin Ala 157 Cys mutant, a small molecule inhibitor (SMI) of integrins αv β3 /αv β5, and a potent cytotoxin, auristatin F (AF). The conjugates selectively and potently inhibited proliferation of tumor cells expressing the target integrins. We anticipate that the small molecule–RIP bioconjugate approach can be broadly applied using other small molecule drugs.